2016
DOI: 10.14710/jgi.5.1.34-41
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh suplementasi taburia (sprinkle) terhadap kadar hemoglobin balita gizi kurang usia 3-5 tahun di Kecamatan Lewimunding Kabupaten Majalengka

Abstract: Background (10,95 ± 0,71 mg/dl) to (11,81 ±0,53 mg/dl)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Ummi study 2019 found the effect of giving taburia supplements on the number of short children where at first the number of short children was 271 then in the fifth month it became 207 people if the percentage from the beginning until the fifth month that is 40.% to 43.9%. Height from the start of treatment to the fifth month increased 1.43 cm (Budiana et al, 2016).…”
Section: Provision Of Additional Recovery Food For Malnourished Child...mentioning
confidence: 95%
“…Ummi study 2019 found the effect of giving taburia supplements on the number of short children where at first the number of short children was 271 then in the fifth month it became 207 people if the percentage from the beginning until the fifth month that is 40.% to 43.9%. Height from the start of treatment to the fifth month increased 1.43 cm (Budiana et al, 2016).…”
Section: Provision Of Additional Recovery Food For Malnourished Child...mentioning
confidence: 95%